2022
DOI: 10.1080/21670811.2022.2085129
|View full text |Cite
|
Sign up to set email alerts
|

Robots in the News and Newsrooms: Unpacking Meta-Journalistic Discourse on the Use of Artificial Intelligence in Journalism

Abstract: As journalism has grappled with the potentials and boundaries of AI within the industry, journalists have produced plentiful articles detailing experimentation and potential consequences of AIdriven journalism (see, GPT-33, 2020). Accordingly, this article analyzes media coverage (N ¼ 95 articles) of AI in journalism over a 5-year period, starting in 2016 and ending in 2020, to examine prominent themes related to uses, roles, and concerns regarding AI in the newsroom. We sample coverage from 20 US and UK news… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 38 publications
0
13
0
7
Order By: Relevance
“…Las denominaciones han sido diversas, ya sea "periodismo escrito por máquinas" ( Van-Dalen, 2012), "periodismo algorítmico" (Anderson, 2012), "periodismo robotizado" (Clerwall, 2014) o, más comúnmente, "periodismo automatizado" (Graefe, 2016;Moran;Shaikh, 2022), dentro del marco más amplio que ofrecen las prácticas del periodismo computacional y del periodismo asistido por ordenador (Codina;Vállez, 2018;Parratt;Mayoral;Mera, 2021).…”
Section: Ia Y Periodismounclassified
“…Las denominaciones han sido diversas, ya sea "periodismo escrito por máquinas" ( Van-Dalen, 2012), "periodismo algorítmico" (Anderson, 2012), "periodismo robotizado" (Clerwall, 2014) o, más comúnmente, "periodismo automatizado" (Graefe, 2016;Moran;Shaikh, 2022), dentro del marco más amplio que ofrecen las prácticas del periodismo computacional y del periodismo asistido por ordenador (Codina;Vállez, 2018;Parratt;Mayoral;Mera, 2021).…”
Section: Ia Y Periodismounclassified
“…But that outcome is fraught with tensions because actors outside the journalistic field have largely supported these technologies with demands foreign to fact-checkers' standards. As this research has shown, when journalists abdicate an active role in the development of AI products, they end up acquiescing to a conflict of interest between their professional needs and those coming from the tech industry, a trend that has also been discussed in recent work on automated journalism (Ford & Hutchinson, 2019;Moran & Shaikh, 2022;Simon, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…As new robots have been put in motion by fact-checkers, even in countries struggling with an acute economic crisis (such as Brazil), it is critical to ask how professionals can keep their autonomy while facing automation demands. Although fact-checking has been linked with innovative trends in digital journalism toward machine-readable forms of writing (Graves & Anderson, 2020;Johnson, 2023), this does not imply that practitioners must embrace every new technology as inevitable to improve their daily work (Moran & Shaikh, 2022). National and regional fact-checking communities should engage in ongoing discussion (beyond global fact-checking annual meetings) regarding the pertinence of introducing new AI products into their workflows, weighing their pros and cons concerning the systems' training demands and the staff and skillset required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations